Design of a Hierarchical Fuzzy Control System to Guide the Robot and Prevent Collisions with Obstacles - Alireza Makvandi; Hesam Makvandi; Sayed Ehsan Alavi (مجله مدل سازی در مهندسی)
Among the advantages of utilizing fuzzy control as an intelligent controller, one can name the elimination of the need for repetitive calculations as well as the ability to use the experience of experts in controlling the robots' motions in uncharted environments. Instead of solving an optimization problem or formulating rules, the fuzzy control method can transfer these rules irregularly to a robot or a group of robots. The fuzzy controller proposed in the current contribution consists of three agents: A robot navigation agent, which helps the robot reach the target point using a fuzzy-based controller, an obstacle avoidance agent which exploits a hierarchical fuzzy control to keep the robot away from obstructions, and a perception agent that employs eight sensors to provide the required information concerning the environment. A value function is proposed to coordinate the aforementioned factors eliminating possible conflict scenarios. The simulation results confirm the effectiveness and efficiency of the proposed approach. Moreover, it is shown that the robot can reach the target point without colliding with obstacles.